The type locality of Scinax dolloi (Werner, 1903) (Anura, Hylidae) - Caramaschi, Ulisses; Nunes, Ivan; Nascimento, Luciana B.; Carvalho Jr, Ronald R. (Zootaxa, 2013)
Hyla dolloi was described by Werner (1903) based on two female specimens housed at the Institut Royal des Sciences Naturelles in Brussels, Belgium (IRSNB 6481). The locality of these syntypes was referred as Brasilien (leider nicht genauer bekannt), in free translation, Brazil (unfortunately nothing more precise is known). Since then, the type locality of the species was generically cited as in the original description (e.g., Nieden 1923; Harding 1983), as “Brasil” (e.g., Bokermann 1966; Duellman, 1977; Frost 1985), or “Brazil” (e.g., Lutz 1973). Moreover, besides treated as a “Doubtful species” by Lutz (1973), Hyla dolloi was considered a “name not associated with any known species” in a note by W.E. Duellman presented in Frost (1985). The combination Scinax dolloi (Werner, 1903) was established by Faivovich et al. (2005) and the species was included in the Scinax ruber clade, among the species not assigned to a species group, although considering that Scinax dolloi, S. hayii, and S. perereca form a morphologically similar group of species.